ChemInform Abstract: Advancements in Oxazolidinone Synthesis Utilizing Carbon Dioxide as a C1 Source. Issue 21 (27th May 2014) - Pulla, Sharon; Felton, Charlette M.; Ramidi, Punnamchandar; Gartia, Yashraj; Ali, Nawab; Nasini, Udaya B.; Ghosh, Anindya
Abstract Review: 52 refs.